Cancellable Insider Trading Plans: An Analysis of SEC Rule 10b5-1* - Lenkey, Stephen L (Review of Financial Studies, 2019)
Abstract Rule 10b5-1 enables insiders to preplan future trades before becoming informed. Within a strategic rational expectations equilibrium framework, I characterize an insider’s unique optimal trading plan, which balances portfolio diversification against exploitation of the rule’s selective termination option. Because the rule reduces adverse selection and provides insurance against bad outcomes, the rule generally improves welfare for both the insider, who later becomes informed, and uninformed outsiders, provided there exists a sufficient degree of information asymmetry. Eliminating the rule’s selective termination option results in an even greater welfare improvement under a large subset of parametric conditions. Received March 9, 2018; editorial decision January 11, 2019 by Editor Wei Jiang.